MODEL PINTAR BERBANTUAN MEDIA TEKATECH : Solusi Inovatif Meningkatkan Keterampilan Berpikir Kritis dan Berkolaborasi Siswa Kelas IV SDN Kelayan Dalam 7 Banjarmasin - Helsa Putri, Nurin Nabilah; Refia Rafianti, Wahdah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The research problem is the low critical thinking and collaboration skills of students, which are caused by one-way learning and monotonous teaching methods. The effort to address this issue involves using the PINTAR model and TEKATECH media. The objective of the research is to analyze the activities, critical thinking skills, and collaboration among students. This study employs Classroom Action Research (CAR). The subjects of the research are fourth-grade students from SDN Kelayan Dalam 7 Banjarmasin. The study utilizes both qualitative and quantitative approaches. The results indicate that the teacher's activity from meetings 1 to 4 improved from a good qualification to very good. The critical thinking skills of students from meetings 1 to 4 increased from a qualification of very few skilled students to almost all students being very skilled. The collaboration skills of students from meetings 1 to 4 also improved from a qualification of very few skilled students to almost all students being very skilled. Based on these findings, it is concluded that the PINTAR model and TEKATECH media are recommended as alternative models for enhancing critical thinking and collaboration skills, as well as the quality of learning.